VALUES AS A PROBLEM OF POLICY: A STATE OF SCIENTIFIC RESEARCH AND INFLUENCE ON POLITICAL ACTIVITY - Климончук, В. Й. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The content, features of manifestation, mechanisms of formation of political dimensions of values in conditions of formation the democratic principles of power are investigated. A special place is given to the analysis of the dynamics of social factor in the context of the transformation of the value definitions of human life. These value definitions are determined by complex globalization processes. A system of values that makes it possible to determine the level of society development (historical, civilizational, cultural, social, political) as a whole, the potentialities of its progression, the state of formation of social and political ideals is characterized.